COMPARISONAL ANALYSIS OF KUZ-RAM METHOD WITH ROCK ENGINEERING SYSTEM ON FRAGMENTATION DISTRIBUTION SIZE ON MOUNT REGO, KULON PROGO REGENCY SPECIAL REGION OF YOGYAKARTA - Suratman, Wanda (ReTII, 2022)
Activities in andesite mining carried out by PT.X using the Quarry system and one of the main activities in andesite mining is blasting. The success of a blast is usually measured by the size of the blasting fragmentation carried out. The size of the fragmentation is expected not to cause much difficulty, batik in loading, transporting, and in crushing activities. The methodology of this research is to use a theoretical method by comparing the two Kuz-Ram methods and the theoretical Rock Engineering System to find out the theoretical percentage results of each method from the actual geometric data obtained in the field, then relate the average size of the fragmentation determined based on the capabilities of the tool. crushers. The average rock escape rate of the Kuz-ram method is 76.369 percent with 23.631 percent retained rock still has rock size that does not pass the sieve above 20 percent. The rock pass rate of the Rock Engineering system method on average is 76.369 percent with 23.631 percent retained rock, there is still rock size that does not pass the sieve above 20 percent. The results of the comparison of the Kuz-Ram method and the Rock Engineering System obtained that the average rock escape value was greater than Kuz-ram with a value of 76,369 percent compared to the Rock Engineering System of 61,139 with an average pass value of below 80 percent.